2010
DOI: 10.1051/0004-6361/201014591
|View full text |Cite
|
Sign up to set email alerts
|

TheHerschelview of GAS in Protoplanetary Systems (GASPS)

Abstract: The Herschel GASPS key program is a survey of the gas phase of protoplanetary discs, targeting 240 objects which cover a large range of ages, spectral types, and disc properties. To interpret this large quantity of data and initiate self-consistent analyses of the gas and dust properties of protoplanetary discs, we have combined the capabilities of the radiative transfer code MCFOST with the gas thermal balance and chemistry code ProDiMo to compute a grid of ≈300 000 disc models (DENT). We present a comparison… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In Figure 5, bottom panel, we plot the [O I] 63 µm line flux as a function of the UV luminosity (calculated as lower limits from atmosphere models in the range of 1150-2430 Å). For HAe stars, there is a correlation between the [O I] 63 µm flux and the UV luminosity, as reported earlier for a limited sample in Pinte et al (2010) and supported by disc models in Kamp et al (2011) can be a consequence of an increase in OH photo-dissociation in the disc surface and/or close to the star, therefore a PDR emission result from the UV irradiation of the outflow. In addition, the data presented in this paper -enhanced [O I], [C II] and CO lines, as well as the presence of water lines-show clear evidence for emission from the shocked material due to the presence of the outflow, which can add up to the [O I] emission from the disc.…”
Section: [O I] and [C Ii]supporting
confidence: 81%
“…In Figure 5, bottom panel, we plot the [O I] 63 µm line flux as a function of the UV luminosity (calculated as lower limits from atmosphere models in the range of 1150-2430 Å). For HAe stars, there is a correlation between the [O I] 63 µm flux and the UV luminosity, as reported earlier for a limited sample in Pinte et al (2010) and supported by disc models in Kamp et al (2011) can be a consequence of an increase in OH photo-dissociation in the disc surface and/or close to the star, therefore a PDR emission result from the UV irradiation of the outflow. In addition, the data presented in this paper -enhanced [O I], [C II] and CO lines, as well as the presence of water lines-show clear evidence for emission from the shocked material due to the presence of the outflow, which can add up to the [O I] emission from the disc.…”
Section: [O I] and [C Ii]supporting
confidence: 81%
“…Results from some subsets of the GASPS study have been presented in previous papers. A summary of the 'science demonstration' observations of a small number of targets was given in Mathews et al (2010), and a comparison of these data with a broad grid of disk models was shown by Pinte et al (2010) In most of the older gas-poor systems the lines were not detected, however, the far-IR photome-try has been used to improve the SEDs and dust modeling (Donaldson et al 2012;Lebreton et al 2012).…”
Section: First Resultsmentioning
confidence: 99%
“…To understand how much the disk can contribute to the extended [O i] and [C ii] atomic lines and to the unresolved molecular emission, we compare observed line fluxes and ratios with predictions from the DENT grid of disk models Pinte et al 2010;Kamp et al 2011). The DENT grid consists of 300 000 disk models spanning a large range of parameters defining the source (mass, M * , temperature, T e f f , luminosity, L * , UV excess) and the disk (disk gas mass, gas-to-dust ratio, inner and outer disk radius, R in , R out , surface density, flaring, dust grain size distribution, dust settling, disk inclination) properties.…”
Section: Emission From Disksmentioning
confidence: 99%